1971
DOI: 10.1029/jc076i024p05799
|View full text |Cite
|
Sign up to set email alerts
|

Field-enhanced propagation of corona streamers

Abstract: Experiments are described in which the lengths of positive and negative streamers, propagating within a region characterized by a uniform electric field, are determined as a function of field strength. Streamers were generated from the application of a short rise‐time voltage pulse to a point electrode and from field‐induced hydrodynamic instability of a falling water drop. Positive streamers display marked length enhancement with ambient electric fields in the direction of propagation greater than about 6×105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 15 publications
(11 reference statements)
5
46
0
Order By: Relevance
“…It has been shown that the stability field is equivalent to the average field along the streamer extension [20]; therefore, if the average field is fixed, the corona length is directly given by the geometric construction of Fig. 6.…”
Section: Corona Propagationmentioning
confidence: 99%
“…It has been shown that the stability field is equivalent to the average field along the streamer extension [20]; therefore, if the average field is fixed, the corona length is directly given by the geometric construction of Fig. 6.…”
Section: Corona Propagationmentioning
confidence: 99%
“…Our assessment of the experience gained since Franklin's time is that sharp rods exposed in isolation on church steeples and other high towers are often struck by lightning whereas similarly sharp Franklin rods installed with lesser isolation are sometimes not struck, other objects in the vicinity being the strike receptors. Phelps [1971] a radioactive "ESE" device and two strikes were also adjacent to a sharp, high-tech, French "air terminal" (which was tested for only a three year period).…”
mentioning
confidence: 99%
“…This equipment has given values in excess of 4 x 105 V 1m (Winn & Moore, personal communication) a value appreciably larger than that obtained by Gunn and one that, when corrected for atospheric pressure, closely approaches the value of electric fields observed by Phelps (41) to be necessary to sustain positive streamer development.…”
Section: Electric Fields In Cloudsmentioning
confidence: 83%